Farming patterns and factors affecting rice farming income on various types of lebak swamp land in Kalidoni Sub-District, Palembang City - Yunita Yunita; Trissa Silvian; Dwi Putri Maharani (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2026)
Rice farming in Indonesia plays a strategic role in ensuring national food security and is a key sector for improving farmers’ welfare, especially in rural areas. The study aimed to analyze the factors influencing rice farmers’ income based on the typology of lebak swamp land, with a focus on Sungai Selincah Urban Village, Kalidoni Sub-District. The objectives were to describe rice farming patterns based on lebak swamp land typology, to analyze total farming income by land type, and to identify key determinants of income across different land typologies. The research location was selected purposively, and data were collected through a survey of 60 respondents. Data were analyzed using descriptive statistics and multiple linear regression. The results show that rice farming practices vary according to land typology, significantly affecting income levels. Among the three land types, farmers on middle lebak swamp land earned the highest income at 45,627,037 IDR/year (3,802,253 IDR/month), categorized as 'very high'. Farmers on shallow lebak swamp land earned 33,306,153 IDR/year (2,775,512 IDR/month), categorized as 'high'. Meanwhile, those on deep lebak swamp land earned 20,651,753 IDR/year (1,720,979 IDR/month), categorized as 'moderate'. The regression results indicate that land area, production volume, and farming experience positively and significantly affect income (p<0.05). Furthermore, compared to deep lebak swamp land (as the reference category), farmers cultivating shallow lebak swamp land and middle lebak swamp land types earned significantly higher income, indicating a substantial income differential across land typologies.